INCLUSIVE PHYSICAL EDUCATION FOR CHILDREN WITH DEVELOPMENTAL DELAYS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article comprehensively examines inclusive approaches to physical education aimed at ensuring the full and equal participation of children with developmental disabilities in physical education programs. Physical, social and emotional impacts, difficulties encountered and proposed solutions are considered in detail.